A Cryogenic Hydrogen Ribbon for Laser Driven Proton Acceleration at Hz-Level Repetition Rate - Chagovets, T.; Viswanathan, J.; Tryus, M.; Grepl, F.; Velyhan, A.; Stancek, S.; Giuffrida, L.; Schillaci, F.; Cupal, J.; Koubikova, L.; Garcia, D.; Manzagol, J.; et al. (Frontiers in Physics, 2022)
We report on recent progress in deploying a continuous solid hydrogen ribbon as a debris-free and renewable laser-driven source of pure proton beams generated by a 30-fs laser with ∼1-J laser energy focused on target at relativistic intensities of ∼1019 W/cm2 and repetition rate of 0.1 Hz. The stability of the ribbon position versus the laser interaction point and maximum repetition rate was tested up to 3.3 Hz. The acceleration of protons with cut-off energies up to 1.5 MeV is demonstrated using a 100-μm thick hydrogen ribbon as proof-of-principle capability of the relatively thick target delivery system. The laser-target geometry presented demonstrates an experimental technique that can potentially enables the operation of a laser–plasma source at Hz-level repetition rate.